Study on the Meshing Theory of End-face Worm Drive - Chen Yan; Gong Yuxia (Jixie chuandong)
Use the space meshing theory to study the meshing theory of end-face worm drive,all of the worms systematically are discussed,the unified formula for the worm wheel tooth surfaces is presented. The unified formulas of the end-face worm drive meshing performance are deduced. Though an example,the meshing performance of end-face worm drive is analyzed. Thus a foundation is laid for the research and manufacture of end-face worm drive and the development of CAD system.